Evaluation of excision of the sublingual grand as a treatment of ranula - Minami, Toyohiko; Nakagawa, Nobuko; Ino, Chiyonori; Yamashita, Toshio (JOURNAL OF JAPAN SOCIETY FOR HEAD AND NECK SURGERY, 2001)
We show our treatment plan for ranula, and discuss evaluation of exision of the sublingual grand. Our treatment plan for sublingual ranula is that we explain both a simple treatment method and a radical one (that is excision of the sublingual gland), whether it is the first onset or reccurence, and finally it depends on the patients decision which treatment is chosen. In case of plunging ranula we first perform puncture and pressure treatment for all of them as simple treatment, and cases of reccurence can choose between another simple treatment, and radical one (excision of the sublingual gland). The subjects of our investigation are 35 cases of sublingual ranula and 12 cases of plunging ranula who visited Kohri Hospital of Kansai Medical University for the past 5 years. Excision of the sublingual gland was performed on 25 of the 35 cases of sublingual ranula and 7 of the 12 csses of plunging ranula. These has been no reccurence in all cases.